2017
DOI: 10.1038/ng.3949
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 153 new loci associated with heel bone mineral density and functional involvement of GPC6 in osteoporosis

Abstract: Osteoporosis is a common disease diagnosed primarily by measurement of bone mineral density (BMD). We undertook a genome-wide association study in 142,487 individuals from the UK Biobank to identify loci associated with BMD estimated by quantitative ultrasound of the heel (“eBMD”). We identified 307 conditionally independent SNPs attaining genome-wide significance at 203 loci, explaining approximately 12% of the phenotypic variance. These included 153 novel loci, and several rare variants with large effect siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
459
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 413 publications
(494 citation statements)
references
References 65 publications
17
459
1
1
Order By: Relevance
“…Common variants intersecting SMAD9 associate with population-based measures of eBMD, as evidenced recently by fine-mapping of target genes (17,44) and from our gene-based tests of association presented here. Common variants intersecting SMAD9 associate with population-based measures of eBMD, as evidenced recently by fine-mapping of target genes (17,44) and from our gene-based tests of association presented here.…”
Section: Discussionsupporting
confidence: 79%
“…Common variants intersecting SMAD9 associate with population-based measures of eBMD, as evidenced recently by fine-mapping of target genes (17,44) and from our gene-based tests of association presented here. Common variants intersecting SMAD9 associate with population-based measures of eBMD, as evidenced recently by fine-mapping of target genes (17,44) and from our gene-based tests of association presented here.…”
Section: Discussionsupporting
confidence: 79%
“…For the 149 genes located in the 32 genome-wide-significant loci ( r 2 >0.5 in Europeans or East Asians, or located ±50 kb from the lead SNP; Methods), we assigned an empirical functional score based on the presence and number of eQTLs, meQTLs, pQTLs, and other biological criteria 57,58 (Methods and Supplementary Table 24), reasoning that genes with a higher functional score would be more likely to be causal, although this score requires validation by experimental data.…”
Section: Resultsmentioning
confidence: 99%
“…Kemp et al [5] recently reported a largest genome-wide association study (GWAS) of BMD as estimated by quantitative ultrasound of the heel in 142,487 individuals from the UK Biobank. The summary results are publicly available in the GEFOS website.…”
Section: Methodsmentioning
confidence: 99%
“…Genome-wide association study (GWAS) and their meta-analysis are a powerful approach to identify common variants associated with complex traits including BMD. In the past decade, over one hundred BMD loci have been discovered by a number of GWAS studies [47], explaining 12% of BMD heritability [5]. However, the explained heritability only accounts for one-third of GWAS-attributable heritability [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation